Sustainability Analysis of Coffee Farming in Protected Forestof West Lampung Based on Enviromental Economic Value - Fembriarti Erry Prasmatiwi; Irham Irham; Any Suryantini; Jamhari Jamhari (Indonesian Coffee and Cocoa Research Institute, 2010)
Study on sustainability of multistrata coffee systems is important related to community forest program. This research aims to study: (1) sustainability of coffee farming in protected forest of West Lampung (2) willingness to pay the external cost and its determinant factors. The study was conducted in Sumberjaya, West Lampung Regency from Juni to October 2009. The study used random sampling method with 50 protected forest farmers were interviewed. Extended Cost Benefit Analysis (ECBA) was used to address the purpose (1) while analysis of ordinal logistic regression was to address the purpose (2) Financial analysis showed that coffee farming in protected forest is feasible with NPV of IDR 17,719,505/ha, BCR 1.86 and IRR 24.96%. Coffee with complex multipurpose shade (MPTS, multipurpose tree species) generated highest NPV. Based on ECBA, sustainability depended on externality cost (environmental and social cost). Coffee farming was not sustainable (shown by negative NPV) when externality cost was more than US 536/ha. When externality cost was 458 USD ha-1 year-1 (minimum value) NPV is Rp1.648.633/ha, BCR 1,04 and IRR 26,88. Complex multipurpose shade coffee was the most sustainable among the systems. To sustain the environment, farmers willing to pay external cost in average of Rp475,660/year for soil conservation, planting more shade trees, environmental tax, and reforestation. Based on ordinal logistic regression, farm size, land productivity, household income, household size, and knowledge of forest benefits, positively influencid WTP. Policy of community forest (HKm permit) that require a minimum of 400 trees/ha could improve sustainability of coffee farming.Key words: Coffee farming, sustainable, protection forest, economic value